(untitled) (Research, Society and Development, 2022)
The production of secondary metabolites of high added value by microorganisms has been extensively studied, mainly in the formulation of medium containing agro-industrial residues. Citric acid is a tricarboxylic organic acid obtained through submerged fermentation processes. The Aspergillus genus is considered an excellent producer of bioactive substances of industrial interest. This study aims to determine the rate of citric acid production using four strains of the microorganism (UCP 1099, 1356, 1357, and 1463) in alternative culture mediums containing citrus pomace (pineapple, orange and lemon) from the food industries in the state of Pernambuco, and to compare the results with the production obtained with the standard production medium using computational statistical tools. Assays were carried out with four samples of Aspergillus isolated from Caatinga in three conventional mediums, for 144 h, 37°C, and 180 rpm. The pH variation, sugar consumption, and citric acid production were analyzed. The results showed that the medium-called two e and the sample UCP1357, presented a citric acid production of 7.22g.L-1. After selecting the medium and the best producer microorganisms, production tests were carried out with a medium formulated with citrus fruit residues. The results revealed that all the residues produced citric acid, with the lemon peel being the best of the residues tested (6.91 g.L-1). It appears that there is a possibility of using residues in the formulation of means of production, thus contributing to the reuse of the present nutrients and the reduction of the environmental impact.